A new species of scaly blenny of the genus Labrisomus (Actinopterygii: Labrisomidae) from the tropical West Atlantic - Sazima, Ivan; Carvalho-Filho, Alfredo; Gasparini, João Luiz; Sazima, Cristina (Zootaxa, 2009)
A new species of scaly blenny, Labrisomus conditus sp. n., is described from Fernando de Noronha Archipelago, off northeastern Brazil. It differs from its Western Atlantic congeners by the following combination of characters: nuchal cirri when depressed not reaching dorsal-fin origin, 68 to 73 lateral line scales, first and second dorsal-fin spines slightly shorter than third spine and not flexible, numerous pale dots overall (light blue in life), opercular dark spot with incomplete and diffuse broad pale margin (orange in life). The new species is a territorial bottom-dweller in rocky shores and is found among algae and in crevices at depths from 0.5 to 6 m. Labrisomus conditus sp. n. feeds mostly on crustaceans (crabs, amphipods) and molluscs (snails, bivalves). The new species increases to five the species within the genus Labrisomus recorded from Southwestern Atlantic.